Bioinsecticide-based malaria control strategy: epidemiological implications and environmental sustainability - Mei Ahyanti; Prayudhy Yushananta (International Journal of Advances in Applied Sciences, 2026)
Anopheles mosquitoes are the main vector of malaria, which remains a global health problem. This study aims to evaluate the effectiveness of various types of plants as bioinsecticides on the mortality of Anopheles larvae based on variations in extract concentration and exposure time. The experimental study design used a completely randomized factorial design. The variables were studied in bioinsecticide formula consisting of 66 levels; 3 levels of concentration and contact time to Anopheles larvae. The number of replications was four times following the Foreder formula. The study was conducted at the Parasitology Laboratory from January to June 2025. Findings showed the factors of plant type (p <0.001), extract concentration (p <0.001), and exposure time (p <0.001) had a significant effect on the level of larval mortality. The interaction between plant type and concentration showed a synergistic effect, where the effectiveness of the bioinsecticide increased with the right combination. Longer exposure times also significantly increased the larval mortality rate. The results of this study indicate that the use of plants as bioinsecticides can be a potential alternative in malaria vector control. The study suggests that plant-based bioinsecticides can effectively combat malaria by enhancing effectiveness through synergistic interactions between plant species, extract concentration, and exposure duration.